2021
DOI: 10.1080/21655979.2021.2012406
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Testis developmental related gene 1 promotes non-small-cell lung cancer through the microRNA-214-5p/Krüppel-like factor 5 axis

Abstract: Non-small-cell lung cancer (NSCLC) is a frequent malignancy and has a high global incidence. Long noncoding RNAs (lncRNAs) are implicated in carcinogenesis and tumor progression. LncRNA testis developmental related gene 1 (TDRG1) plays a pivotal role in many cancers. This study researched the biological regulatory mechanisms of TDRG1 in NSCLC. Gene expression was assessed by reverse transcriptase quantitative polymerase chain reaction (RT–qPCR). Changes in the NSCLC cell phenotypes were examined using 5-ethyny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Furthermore, α-Catulin has been reported to promote cancer stemness by antagonizing the WW domain-containing E3 ubiquitin protein ligase 1-mediated degradation of KLF5 in lung cancer ( 19 ). Testis development-related 1 serves a carcinogenic role in non-small cell lung cancer by targeting the microRNA (miR)-214-5p/KLF5 axis ( 20 ). KLF5-induced γ-butyrobetaine hydroxylase 1-antisense RNA 1 has been found to upregulate maternal embryonic leucine zipper kinase expression to activate focal adhesion kinase (FAK) signaling, by sponging miR-27a-5p, contributing to the malignant phenotype of non-small cell lung cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, α-Catulin has been reported to promote cancer stemness by antagonizing the WW domain-containing E3 ubiquitin protein ligase 1-mediated degradation of KLF5 in lung cancer ( 19 ). Testis development-related 1 serves a carcinogenic role in non-small cell lung cancer by targeting the microRNA (miR)-214-5p/KLF5 axis ( 20 ). KLF5-induced γ-butyrobetaine hydroxylase 1-antisense RNA 1 has been found to upregulate maternal embryonic leucine zipper kinase expression to activate focal adhesion kinase (FAK) signaling, by sponging miR-27a-5p, contributing to the malignant phenotype of non-small cell lung cancer ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed that abnormal expression of KLF5 is observed in a number of different types of cancer, such as breast, prostate and bladder cancer (17). Notably, increasing evidence has shown that KLF5 also exerts tumor-promoting activities in lung cancer (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In this article, miR-214-3p targeting of PTEN affected the downstream PI3K/AKT pathway, thereby regulating renal interstitial fibrosis and TGF β -induced EMT ( Figure 4 ). miR-214 was proven to upregulate the PI3K/AKT pathway by targeting PTEN, thereby protecting cells from damage induced by hypoxia/reoxygenation (H/R) and reducing myocardial damage induced by ischaemia/reperfusion (I/R) and cardiomyocyte apoptosis [ 44 , 45 ]. According to the results of this experiment, there may be a feedback regulatory loop between PTEN and PI3K/AKT in renal fibrosis induced by miR-214, but this conclusion needs further experimental confirmation.…”
Section: Discussionmentioning
confidence: 99%